AI DRIVEN NURSING CARE: EXPLORING THE READINESS AND ACCEPTANCE OF ARTIFICIAL INTELLIGENCE IN CLINICAL NURSING PRACTICE - Prima Auditia; Feri Catur Yuliani (Penelitian dan Pengembangan Ilmu, 2025)
The integration of artificial intelligence (AI) into nursing practice has become an important topic, but nurses’ perceptions of the usefulness and ease of use of this technology remain poorly understood. This study aims to explore how nurses perceive AI in clinical decision-making, as well as the factors that influence their acceptance.This study aims to analyze nurses' perceptions regarding the usefulness and ease of use of AI-based tools in a clinical context, as well as to identify challenges faced in the adoption of this technology.This study uses a systematic literature review (SLR) approach by collecting and analyzing data from peer-reviewed articles published between 2013 and 2024. The selection process follows the PRISMA guidelines, and data analysis is carried out using the thematic synthesis method.Findings indicate that although nurses have positive perceptions of the usefulness of AI in improving accuracy and efficiency, challenges related to ease of use, such as complex interface design and lack of training, hinder the adoption of this technology.This study provides important insights for technology developers and healthcare institutions to design more user-friendly AI systems, and emphasizes the need for better training to increase nurses' acceptance of this technology.